Mechanisms of lymphatic metastasis in human colorectal adenocarcinoma - Royston, Daniel; Jackson, David G. (The Journal of pathology, 2009)
The invasion of lymphatic vessels by colorectal cancer (CRC) and its subsequent spread to draining lymph nodes is a key determinant of prognosis in this common and frequently fatal malignancy. Although tumoural lymphangiogenesis is assumed to contribute to this process, review of the current literature fails to support any notion of a simple correlation between lymphatic vessel density and CRC metastasis. Furthermore, attempts to correlate the expression of various lymphangiogenic growth factors, most notably VEGF‐C and VEGF‐D, with the lymphatic metastasis of CRC have provided contradictory results. Recent evidence from animal and human models of tumour metastasis suggests that complex functional and biochemical interactions between the microvasculature of tumours and other cell types within the tumour microenvironment may play a pivotal role in the behaviour of commonly metastasizing tumours. Indeed, previous insights into tumoural blood vessels have provided candidate markers of tumoural angiogenesis that are currently the subject of intense investigation as future therapeutic targets. In this review article we survey the current evidence relating lymphangiogenesis and lymphangiogenic growth factor production to metastasis by CRC, and attempt to provide some insight into the apparent discrepancies within the literature. In particular, we also discuss some new and provocative insights into the properties of tumoural lymphatics suggesting that they have specific expression profiles distinct from those of normal lymphatic vessels and that appear to promote metastasis. These findings raise the exciting prospect of future biomarkers of lymphatic metastasis and identify potential targets for new generation anti‐tumour therapies. Copyright © 2009 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.